Application of the Concept Teaching Model with the Direct Resentation Approach to Increase the Activities and Results of Science Learning for Class VIIA SMP Negeri 4 Kendari on Material Forms of Substance - Lukman (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2022)
Abstract The aim of the research is to apply the concept teaching model with the direct presentation approach to increase the activities and learning outcomes of science students in grade VII SMP Negeri 4 Kendari on the matter of matter. This type of research is Classroom Action Research (CAR) with two learning cycles, with stages: planning, implementing the action, observation, evaluation, and reflection. Data were collected using learning achievement tests and teacher and student observation sheets, which were then analyzed using descriptive analysis. The success of the action of the first cycle of student activities achieved a score with an average of 2.52 in the second cycle, namely 3.78. The success of teacher activity actions in cycle I achieved an average score of 3.04, and cycle II reached 3.92. The average achievement of student learning outcomes in the first cycle reached 53.52; in the second cycle reached 72.76. Based on the results of the study, it was concluded that the application of the concept teaching model with the direct presentation approach could increase the activities and learning outcomes of science students in class VIIA SMP Negeri 4